State budget of USSR in 1950s — 80s: dynamics and structure of expenditures - S. A. Bakanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The structure of the state budget expenditure of the USSR in its historical dynamics during the 1950s — 1980s is considered. The sources were statistical collections published by the Ministry of Finance of the USSR in the period under review, on their basis the electronic database “State Budget of the USSR” was created, according to which all the calculations presented in the article were carried out. It is noted that the dynamics of the state budget expenditures of the USSR during the entire period of the 1950s — 80s was positive. It is indicated that there was a constant increase in expenditures, which had an average annual value of about 6.5 %; in total, during the period under study, the expenditure part of the state budget increased by 11.6 times, and in per capita terms only by 7.3 times. It is shown that the structure of expenditures of the state budget of the USSR in the 1950s — 1980s included expenditures on the national economy, social and cultural events, public administration and defense. The author concludes that the construction of a welfare state in the USSR in the 1950s — 1970s, along with the burden of military spending, became a heavy burden on the budget system, limiting the government’s room for maneuver in the context of the budget crisis that broke out in the second half of the 1980s.